DNA Barcoding Reveals Widespread Co-Occurrence of Other Chub Species in the Range of the Endemic Catalan Chub, Squalius laietanus - Núria Pérez-Bielsa; Sandra Heras; Alba Abras; Jose-Luis García-Marín (Diversity)
The Catalan chub, Squalius laietanus, was described in 2007 and has recently reached Vulnerable status on the IUCN Red List of Threatened Species. The assigned range for this species includes the lower course of the Ebro River in Spain and northwards to the Tech, Têt, Agly, and Massane Rivers in Southeastern France. In this study, 246 chub specimens caught at 15 sites in the nine main river basins of the Spanish range were barcoded by sequencing a 624 bp fragment of the mitochondrial COI gene. Squalius laietanus haplotypes were found in 68% of the fish caught. In a tributary of the Ebro River, all specimens (6%) were identified as the Tagus chub, S. pyrenaicus, another endemic Iberian chub species. The remaining fish (26%) had a haplotype typical of the European chub, S. cephalus, populations outside Spain. This haplotype was present in six sites in four basins, being particularly abundant in the Ebro River. Considering that Squalius species can hybridize with other native and non-native cyprinid species, the potential co-occurrence of several species in the same site or basin raises concerns about the real extent of an exclusive range for the Catalan chub and the integrity of its native gene pools throughout its range.